PENGARUH EDUKASI DAN SOSIALISASI TERHADAP TINGKAT PENGETAHUAN DAN UPAYA PENCEGAHAN STUNTING ANAK USIA BALITA DI DESA PASIR PETEUY KECAMATAN CADASARI KABUPATEN PANDEGLANG - Dewi Rahmi Fauziah; Rizka Amelia; Jane Novi Fitria; Nurul Hida; Robi Hermawan (LPPM Universitas Bina Bangsa, 2024)
Stunting is still a problem in Banten Province In 2021, the Indonesian Nutrition Status Study stated that Banten Province experienced an increase in the prevalence of stunting to 24.5%. This value, exceeding the national stunting condition in the same year, actually decreased to 24.4%. The most cases of stunted toddlers are in Pandeglang Regency with a percentage reaching 37.8%. Stunting is a hot and urgent issue to be resolved because it affects the quality of Indonesia's human resources in the future. The purpose of this research is the socialization of stunting carried out by 19 students of Thematic KKN 09 Mathla'ul Anwar University Banten in Pasir Peuteuy village, Cadasari sub-district, Pandeglang. The research method used is a qualitative approach with descriptive analysis. The data source is policy document analysis. Stunting is considered a failure of linear growth in children due to malnutrition over a long period of time. Thematic KKN Group 09 Mathla'ul Anwar University Banten through this activity took the initiative to carry out stunting socialization activities with the aim of increasing community knowledge and knowledge about stunting. Implementation of stunting socialization through 3 stages, namely preparation of facilities and infrastructure, socialization and evaluation stages. The results of the implementation of stunting socialization are the increase in knowledge of the Pasir Peuteuy community, Cadasari sub-district, Pandeglang after being given counseling in the form of socialization from BKKBN